“Our family sleeps deeply”: The Presence of Others During Intrafamilial Child Sexual Abuse as Conveyed By Girls From Diverse Communities in Israel - Klebanov, Bella (Journal of interpersonal violence, 2023)
Child sexual abuse (CSA) is generally perceived as a crime perpetrated out of sight, without witnesses. Nevertheless, several researchers have explored the presence of others during incidents of abuse in regards to two main aspects: bystanders in extrafamilial CSA and bystanders’ decisions whether or not to get involved. However, there is a dearth of knowledge regarding how children who experience abuse perceive and experience the presence of others during abusive incidents. The current study was designed to examine the experiences and perceptions of girls who experienced intrafamilial CSA (IFCSA) with respect to the presence of others, as conveyed during their forensic interviews. A thematic analysis of 24 forensic interviews was conducted with secular Jewish, ultra-Orthodox Jewish, and Muslim Arab girls, aged 4–14. The analysis identified four main themes: (a) the girls’ perceptions of others’ awareness of them being abused, (b) the girl’s experiences of loneliness, (c) the girls’ experiences of disclosing to the others present during the abuse, and (d) family dynamics. The discussion highlights the unique, multifaceted and elusive dynamics of IFCSA, calling into question the commonly held view that it happens only in secret. The girls’ narratives highlighted their distress and pointed to the abusive and unbearable daily routine in which they live. In spotlighting their encounters with IFCSA, the girls focused on the feelings of guilt, shame, and isolation they experienced.